A importância da conformidade das instalações elétricas para a gestão de riscos e prevenção de incêndios em patrimônio cultural edificado - Marcelo Santana Silvino (2018)
This work aims at contributing to the fire risk management presenting a template, in the form of a checklist, which works as a guide for the verification of buildings electrical installations. It also aims at to providing resources to the management of the built cultural heritage, presenting guidelines for interventions to adapt electrical installations that can be considered part of the conservation of the cultural asset. As for the methodology, the research used to collect data a bibliographic review of articles published in journals, preferably the peer reviewed ones, specific regulation of the electric sector, the Minas Gerais Military Fire Brigade legislation and Patrimonial Letters adopted by the Unesco and Icomos. The suggested template and intervention guidelines presented were applied in a case study carried out at Casa da Glória Institute, in Diamantina, a city in the state of Minas Gerais, a national and world heritage site, in which it was possible to verify its feasibility. The results of this work are expected to serve as a tool to reduce the fires related to electricity, and to guide intervention activities in the built cultural heritage and also encourage new research related to the theme.